Potato Cultivation Technology for Increasing Famers Income in Area Exposed to the Eruption of Mount Sinabung, Karo District - Sebayang, Lukas; Mieke Afni Hardyani (Jurnal Online Pertanian Tropik, 2021)
The negative impact of land exposed to the eruption of Mount Sinabung can be improved through the provision of soil amendments and improvement of soil fertility so that the physical and chemical properties of the land are suitable for potato plants. This study aims to compare the potato cultivation technology package recommended by the North Sumatra AIAT with the farmer technology package on land exposed to the eruption of Mount Sinabung. The experiment was conducted in one of the potato production centers that experienced the impact of the eruption in Kutarayat Village, Naman Teran District, Karo Regency, located 3 km from the eruption center from January - December 2019. The treatment of the cultivation technology package studied were: 1). Recommended technology package: Soil processed twice, dolomite 2 tons/ha, manure sown in arrays 20 tons/ha, sawdust 5 tons/ha, NPK 500 kg/ha, urea 100 kg/ha, KCl 100 kg/ha; 2). Farmer's technology package: soil is processed once, manure in holes 10 tons/ha, NPK 250 kg/ha, urea 100 kg/ha, KCl 100 kg/ha. The results of the study showed that: (1) the growth of potato plants that received the recommendation package cultivation technology treatment was better than the farmers' technology package. (2) potato tuber production with the application of recommended technology resulted in the highest tuber production of 39.81 t/ha, while the farmer's cultivation technology package was 23.79 t/ha. (3) Likewise, the weight of large tubers (> 200 g/tuber ) was significantly higher and more abundant than the farmers' technology package. Potato planting with the recommendation package input resulted in the highest tuber production of 39.81 t/ha. Economically profitable with a B/C ratio of 2.69. Key words: Potato, eruption, mount Sinabung, technology package